2022
DOI: 10.1039/d1cp05840a
|View full text |Cite
|
Sign up to set email alerts
|

Probing the molecular structure of aqueous triiodide via X-ray photoelectron spectroscopy and correlated electron phenomena

Abstract: Liquid-microjet-based X-ray photoelectron spectroscopy was applied to aqueous triiodide solutions, I3(aq.)-, to investigate the anion's valence- and core-level electronic structure, ionization dynamics, associated electron-correlation effects, and nuclear geometric structure. The...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 93 publications
5
22
1
Order By: Relevance
“…Liquid jet X-ray photoelectron spectroscopy is another powerful tool to probe surface composition, but this technique may give different results compared to this SFG study, as in the liquid jet, the surface is generated quasi-instantaneously, and we expect the generation of I 3 − to be slower than the time scale of the surface generation in these types of experiments. 35,38 ■ ENVIRONMENTAL IMPLICATIONS Here, by combining PD-HD-SFG spectroscopy with AIMD simulation, we confirmed that the iodide ion does not significantly reduce the contact area of the N 2 gas−water interface; iodide ions are instead located below the topmost water layer. When the iodide ion concentration increases, the triiodide ions are more present at the vapor−water interface, resulting in a ∼10 8 times higher concentration at the surface than in bulk.…”
supporting
confidence: 60%
“…Liquid jet X-ray photoelectron spectroscopy is another powerful tool to probe surface composition, but this technique may give different results compared to this SFG study, as in the liquid jet, the surface is generated quasi-instantaneously, and we expect the generation of I 3 − to be slower than the time scale of the surface generation in these types of experiments. 35,38 ■ ENVIRONMENTAL IMPLICATIONS Here, by combining PD-HD-SFG spectroscopy with AIMD simulation, we confirmed that the iodide ion does not significantly reduce the contact area of the N 2 gas−water interface; iodide ions are instead located below the topmost water layer. When the iodide ion concentration increases, the triiodide ions are more present at the vapor−water interface, resulting in a ∼10 8 times higher concentration at the surface than in bulk.…”
supporting
confidence: 60%
“…32−35 A model system which has been utilized to observe ultrafast bond cleavage and recombination has been the photodissociation of triiodide, I 3 − + hν → I 2 − + I. 36−39 Due to its seemingly simple dissociation reaction involving only three solute atoms, it has been extensively investigated using a manifold of techniques, including absorption, 36,39,40 Raman, 41 and photoelectron spectroscopy 42 as well as TR-XSS 43 and electron diffraction. 44 The photodissociation of I 3 − (I 3 − → I 2 − + I) takes place upon photoexcitation into one of the two broad absorption bands centered around 290 and 360 nm (Figure S1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The former describes the recombination of fragments directly inside the first layer of solvent molecules within a few picoseconds. In secondary geminate recombination, the fragments are separated by a few layers of solvent molecules, also referred to as “contact pair”, leading to recombination on tens to hundreds of picoseconds. A model system which has been utilized to observe ultrafast bond cleavage and recombination has been the photodissociation of triiodide, I 3 – + h ν → I 2 – + I. Due to its seemingly simple dissociation reaction involving only three solute atoms, it has been extensively investigated using a manifold of techniques, including absorption, ,, Raman, and photoelectron spectroscopy as well as TR-XSS and electron diffraction …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations